Continuidade e ruptura nos padrões de localização do terciário superior no setor sudoeste de São Paulo - Dinis, Henrique (2010)
This thesis shows how the road system had a vital importance in the São Paulo urban development process, toward the Southwest, resulting in a new business center of upper tertiary services. Are identified the characteristics of this process, and their relationships with this expansion. Also, evaluates the differences with similar planning processes. Historically, reference events that are relevant to the economic transformations along the city's growth, from its industrial phase to a metropolis and global city, marked by continuities and ruptures, concerning location patterns of upper tertiary activities. Finally, the thesis identifies the Southwest sector as the main area of services in the city. Also had importance in analyses, as a result of this process, changes of continuous pattern of urbanization, that developed a model, where the urbanization decentralized assumed a primary role, peculiar characteristic of metropolitan cities.